d+87=11(1-d)+12d+76

Simple and best practice solution for d+87=11(1-d)+12d+76 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for d+87=11(1-d)+12d+76 equation:


Simplifying
d + 87 = 11(1 + -1d) + 12d + 76

Reorder the terms:
87 + d = 11(1 + -1d) + 12d + 76
87 + d = (1 * 11 + -1d * 11) + 12d + 76
87 + d = (11 + -11d) + 12d + 76

Reorder the terms:
87 + d = 11 + 76 + -11d + 12d

Combine like terms: 11 + 76 = 87
87 + d = 87 + -11d + 12d

Combine like terms: -11d + 12d = 1d
87 + d = 87 + 1d

Add '-87' to each side of the equation.
87 + -87 + d = 87 + -87 + 1d

Combine like terms: 87 + -87 = 0
0 + d = 87 + -87 + 1d
d = 87 + -87 + 1d

Combine like terms: 87 + -87 = 0
d = 0 + 1d
d = 1d

Solving
d = 1d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-1d' to each side of the equation.
d + -1d = 1d + -1d

Combine like terms: d + -1d = 0
0 = 1d + -1d

Combine like terms: 1d + -1d = 0
0 = 0

Simplifying
0 = 0

The solution to this equation could not be determined.

See similar equations:

| 12-7x-4-x=11-8x+2x | | 10x^2+5x+1=10 | | 10x^2+5x+5=0 | | 6/g=3 | | 10x^2+5x+1=0 | | z=0.5y*x^2 | | 2x^34=50 | | -1+9=3b-7-2b | | 6x+2x+5=2x | | cos(x+5)=sin(3x+9) | | [x-3]=2x+5 | | pq^2+pq+p^2q= | | 6x^3-9x^2-36x+8=0 | | 5y^2+40y-75=0 | | .28x=2556.36 | | 4+6=446 | | 4n-24=56 | | 5x-55=-130 | | 5n+5-7n=15-12n+10n-10 | | 0.5(4x-8)=6x+10 | | 3G+24=9f | | -8x^2+12x+2=4x | | (x+1)(x+2)(x-2)=x^3+8 | | t*3-4=15 | | 9xy/7= | | -58+5y+4=3(4y-3)-3 | | 7m-22=32 | | 3/(w-3)-3/5=w/(w-3) | | 4x+5x=2 | | y^-2=4/16 | | x^2+2x^2=80 | | 5n+11=21 |

Equations solver categories